Marketing research : an applied approach - Malhotra Naresh K. (Prentice Hall/Financial Times, 2007)
This text presents a look at both the principles and practices of marketing research with balanced coverage of qualitative and quantitative material. Written from the perspective of market research users, it reflects current trends in international marketing, ethics, and the continuing integration of technology